MATERNAL ADIPOKINES AND INSULIN AS BIOMARKERS OF OBSTETRIC AND PERINATAL PATHOLOGY IN OVERWEIGHT WOMEN - Ostafiichuk, S.O.; Henyk, N.I.; Neiko, O.V.; Snizhko, T.B.; Rymarchuk, M.I.; Vdovichenko, Yu.P. (World of Medicine and Biology, 2022)
Overweight women have an increased risk of decreased insulin sensitivity compared to normal weight women. In the study, it was shown that excessive gestational weight gain in prepregnancy overweight women is positively associated with increased production of leptin, resistin, and insulin, which are markers of insulin resistance and play an important role in the pathophysiology of gestational complications. It was proved that the chances of hyperleptinemia and hyperresistinemia increased in pregnant women with gestational hypertension and preeclampsia, especially in women with excessive gestational weight gain. In pregnant women with fetal growth retardation chances of insufficient leptin elevation in the second trimester increased in insufficient weight gain patients. A strong relationships between the concentration of leptin and resistin and the insulin resistance index in 22–24 weeks (r=0.83, p=0.000) and (r=0.83, p=0.000) and 37–39 weeks (r=0.86, p=0.000) and (r=0.84, p=0.000) were studied respectively. Due to insulin resistance, overweight women are at increased risk of metabolic dysregulation in pregnancy and associated negative results for the mother and fetus.